Faktor-Faktor yang Berhubungan dengan Praktik Pemberian ASI Ekslusif Pada Ibu yang Memiliki Bayi Usia 7-12 Bulan - Mimi Ruspita; Nur Fatimah Lady Maharani (Midwifery Care Journal, 2024)
Exclusive breastfeeding for 6 months is the most optimal way of feeding babies. A pre-survey conducted by interviewing posyandu cadres in the Way Sulan Community Health Center working area revealed that the factors that cause mothers not to breastfeed exclusively include work demands that interfere with the process of exclusive breastfeeding and the absence of support and attention from family or health workers in mother's breastfeeding process. However, these factors have not been tested for their relationships with the practice of giving exclusive breastfeeding. This study aim was to determine employment status, husband's support and health worker’s support, associated with exclusive breastfeeding for mothers who have babies aged 7-12 months in Talang Way Sulan Village, South Lampung. This research is an analytic observational study with a cross sectional design with 90 mothers who have babies aged 7-12 months as respondents which taken by probability sampling technique. The assessment was carried out using a questionnaire that had been tested for validity and reliability before. Data analysis using Chi-Square. The results showed that there was a relationship between the mother's work and exclusive breastfeeding (p=0.005), husband's support and exclusive breastfeeding (p=0.000), also the health worker’s support and exclusive breastfeeding (p=0.002). It is hoped that this can become a reference for breastfeeding mothers, families, health workers and the government in overcoming exclusive breastfeeding coverage which has not yet reached the target